Treatment planning and evaluation of gated radiotherapy in left-sided breast cancer patients using the CatalystTM/SentinelTM system for deep inspiration breath-hold (DIBH). Issue 1 (December 2016) - Schönecker, S.; Walter, F.; Freislederer, P.; Marisch, C.; Scheithauer, H.; Harbeck, N.; Corradini, S.; Belka, C.
Abstract Background There is a potential for adverse cardiovascular effects in long-term breast cancer survivors following adjuvant radiotherapy (RT). For this purpose, the deep inspiration breath-hold technique (DIBH) has been introduced into clinical practice, to maximally reduce the radiation dose to the heart. However, there are a variety of DIBH delivery techniques, patient positioning and visual patient feedback mechanisms. The aim of the present study was to evaluate the application of radiotherapy in DIBH using the CatalystTM /SentinelTM system, with a special emphasis on treatment planning and dosimetric plan comparison in free breathing (FB) and DIBH. Patients and methods A total of 13 patients with left-sided breast cancer following breast conserving surgery were included in this prospective clinical trial. For treatment application the CatalystTM /SentinelTM system (C-RAD AB, Uppsala, Sweden) was used and gating control was performed by an audio-visual patient feedback system. CT and surface data were acquired in FB and DIBH and dual treatment plans were created using Pencil Beam and Collapsed Cone Convolution. Dosimetric output parameters of organs at risk were compared using Wilcoxon signed-rank test. Central lung distance (CLD) was retrieved from iViewTM portal images during treatment delivery. Results The system contains a laser surface scanner (SentinelTM ) and an optical surface scanner (CatalystTM ) interconnected to the LINAC systems via a gating interface and allows for a continuous and touchless surface scanning. Overall, 225 treatment fractions with audio-visual guidance were completed without any substantial difficulties. Following initial patient training and treatment setup, radiotherapy in DIBH with the CatalystTM /SentinelTM system was time-efficient and reliable. Following dual treatment planning for all patients, nine of 13 patients were treated in DIBH. In these patients, the reduction of the mean heart dose for DIBH compared to FB was 52 % (2.73 to 1.31 Gy;p = 0.011). The maximum doses to the heart and LAD were reduced by 59 % (47.90 to 19.74 Gy;p = 0.008) and 75 % (38.55 to 9.66 Gy;p = 0.008), respectively. In six of the nine patients the heart completely moved out of the treatment field by DIBH. The standard deviation of the CLD varied between 0.12 and 0.29 cm (mean: 0.16 cm). Conclusion The CatalystTM /SentinelTM system enabled a fast and reliable application and surveillance of DIBH in daily clinical routine. Furthermore, the present data show that using the DIBH technique during RT could significantly reduce high dose areas and mean doses to the heart. Trial registration DRKS: DRKS00010929 registered on 5. August 2016.